Mobilização social no Facebook: conectando solidariedade e justiça no caso da Boate Kiss - Silva, Carolina Moro da (2014)
The research takes into account the penetration of information and communication technologies in all spheres of human activity and the configuration of logic networks as central to contemporary social organization. In this context, the study focuses on the communication phenomenon of online social networks for social mobilization in the case of the tragedy of Kiss Nightclub in Santa Maria - RS. Therefore, we built our research problem in seeking to understand how and by whom collective identities were constructed in social mobilizations organized by Facebook around the tragedy of Nightclub Kiss. Therefore, the main objective of the research was to investigate the collective identities constructed via online social networks in order to identify the role of online social networks to organize the protests network. This general objective derives specific: identify generating feelings of these mobilizations and possible implications for the construction of collective identities; was to investigate how this organization, which existing conflicts and how actions were effected by these collectives. The data that make up the cutout of the study were collected through online and offline observations and semi-structured interviews with subjects participating in two mobilizations in the urban area of Santa Maria and from three events created on Facebook as a result of the fire: the Walk to Peace (organized from Facebook events Walk Mourning and Walk to Peace) and Protest for Justice (organized by event Protest for Justice). As a theoretical framework we seek the reflections of researchers of social movements, movements in networks, social movements and social networks like Touraine (2009), Castells (2012), Toro (1996) e Recuero (2009). As a result, we noticed that subjects formed networks to mobilize action through online social network Facebook, promote volunteerism, gather information and encourage debate about the responsibility of the fire. The mobilizations were analyzed based primarily by feelings of solidarity and outrage. In short, organized communication networks, sharing affects, debating positions contrary and uniting to overcome pain in the form of social mobilization actions.